Racism Measurement Framework: A Tool for Public Health Action and Accountability - Saira Nawaz; Kyle J. Moon; Eric Seiber; Anne Trinh; Suellen Bennett; Joshua J. Joseph (Ohio Journal of Public Health, 2020)
Racism is a principal determinant of health inequity, but recent events have galvanized local and state leaders across Ohio to declare racism a public health emergency. In addition to the renewed call to racial justice, sustained progress will require ongoing measurement to determine which anti-racist efforts are working, and why. In this review, we present existing measures categorized by 3 dimensions of racism that interact and build off of one another: (1) systemic racism, considering the health effects of policies in housing, voting, criminal legal system, economic opportunity, and health care; (2) interpersonal racism, and measures of provider bias and cultural competency; (3) internalized racism, measured as allostatic stress and heightened vigilance in distinct contexts. After identifying knowledge gaps, we developed a racism measurement framework that more comprehensively depicts the disparities caused by racism within Ohio and can be used to monitor and evaluate the effectiveness of anti-racist efforts implemented across the state. As such, this framework provides not only a call for action against racism in Ohio, but an opportunity for organizations to measure the extent to which efforts have intervened on supposedly entrenched pathways to health inequities and disparities caused by racism.
Keywords: Racism; Measurement framework; Health outcomes; Evaluation; Health disparities